If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = y + 19 Reorder the terms: 41 = 19 + y Solving 41 = 19 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 41 + -1y = 19 + y + -1y Combine like terms: y + -1y = 0 41 + -1y = 19 + 0 41 + -1y = 19 Add '-41' to each side of the equation. 41 + -41 + -1y = 19 + -41 Combine like terms: 41 + -41 = 0 0 + -1y = 19 + -41 -1y = 19 + -41 Combine like terms: 19 + -41 = -22 -1y = -22 Divide each side by '-1'. y = 22 Simplifying y = 22
| y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 | | .09x+.11(x+9000)=2590 | | 2f=86 | | 33=-3f | | 2.5d+3.25=1+3.25 | | -7-13=9x+18-18x | | -70=7k | | 0=4/15y-28 | | 1/x=7/3 | | 7-8d=39 | | 1.08y=y+48 | | 3x-55+2x=5y | | Y+4.7=-8.6-5.3 | | -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 | | (4f^2-3)+11f=0 | | 5x+18+3x+34=90 | | y-7=-2.66(x-10) | | 42y+16= | | 4(2x+2)+5=3+2(4x+5) | | Z-2.8=10.9 |